Chromosome 3q arm gain linked to immunotherapy response in advanced cutaneous squamous cell carcinoma. (May 2019) - Kacew, Alec J.; Harris, Ethan J.; Lorch, Jochen H.; Haddad, Robert I.; Chau, Nicole G.; Rabinowits, Guilherme; LeBoeuf, Nicole R.; Schmults, Chrysalyne D.; Thakuria, Manisha; MacConaill, Laura E.; Hanna, Glenn J.
Abstract: Aims: The activity that the immune checkpoint inhibitor (ICI) cemiplimab has recently demonstrated has led to a paradigm shift in the management of patients with advanced cutaneous squamous cell carcinoma (cSCC). To identify predictive biomarkers of response to ICIs in advanced cSCC, we studied 33 patients who received ICI therapy at the Dana-Farber/Harvard Cancer Center (DF/HCC) and analysed sequencing data for a subset of these patients. Methods: We collected clinical data using electronic health records and genomic data using the institutional OncoPanel platform of the DF/HCC. We compared tumour genomics with data from previously sequenced cSCC cohorts. Results: We observed high tumour mutational burden regardless of smoking status and response to ICI and longer median overall survival among those patients who achieved an ICI response. We compared the genetic data from our cohort with data from other cohorts that included fewer patients with distant metastatic disease. Although our cohort had a similar genetic landscape to those of comparator cohorts, mutations in PIK3C2B were more common in our study. In our cohort, copy number alterations (CNAs) in the 3q chromosomal arm appeared to predict response to ICI therapy. Conclusion: CNAs in the 21–27 bands of chromosome arm 3q, a region that includes PIK3CA, ETV5 and BCL6, may represent predictors of response to ICI and may be candidates for drug targeting in combination or sequence with ICI agents. Highlights: Alterations in 3q arm genes (e.g. PIK3CA, ETV5 and BCL6 ) may predict ICI response. NF1 mutations may be associated with lower chance of ICI response. PI3K pathway mutations may be associated with increased risk of metastasis. Two kidney transplant patients responded to ICI therapy while on immunosuppression.